1998
DOI: 10.3133/ofr98119
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of the large hydraulic gradient under Yucca Mountain, Nevada

Abstract: We use coupled fluid-and heat-flow modeling (the TOUGH2 code) to investigate three alternative hydrogeologic models for a steep 300-m water-table decline, known as the large hydraulic gradient (LHG), and a spatially coincident heat-flow low under Yucca Mountain, Nevada: (1) a fault-related dam within the volcanic tuff (water-table) aquifer, (2) a spillway created by abrupt southward increase in the depth-extent (thickness) and permeability of the tuff aquifer across a fault, and (3) a drain formed by a fault t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, just to the north of Yucca Mountain, the water table steeply dips, with a drop of almost 300 m in depth over a very short distance. The region termed the Large Hydraulic Gradient region [33], or LHG, has been the subject of considerable study and modeling [32,34]. In its early years, it was suggested that it was a perched water table [35] while now it appears to be considered part of the regional aquifer system.…”
Section: The Underground Waterfallmentioning
confidence: 99%
See 1 more Smart Citation
“…However, just to the north of Yucca Mountain, the water table steeply dips, with a drop of almost 300 m in depth over a very short distance. The region termed the Large Hydraulic Gradient region [33], or LHG, has been the subject of considerable study and modeling [32,34]. In its early years, it was suggested that it was a perched water table [35] while now it appears to be considered part of the regional aquifer system.…”
Section: The Underground Waterfallmentioning
confidence: 99%
“…However, the fact that the anomalous groundwater behavior immediately to the north of the proposed repository is not understood nor has any evidence to support a solid conceptual model adds a significant amount of uncertainty to the general understanding of the groundwater beneath Yucca Mountain. In the early years of Yucca Mountain, the National Academy of Sciences, in reviewing the site conclude: "not until the source of the gradient (the >300 m water table decline) is known can the potential hazard that the repository may face due to climate changes and/or tectonic events be evaluated with a high level of confidence" [33,36]. Its impact on the transport characteristics from Yucca Mountain may not be greatly significant, but it seems critical that major uncertainties, such as what makes the groundwater drop~300 m in 2 km, be explainable and backed by field data.…”
Section: The Underground Waterfallmentioning
confidence: 99%